INSERÇÃO DA ENFERMAGEM DA UNIJUI NO PROJETO ESPAÇO SOLIDÁRIO - Spengler, Rúbia O.; Roncato, Claudia A.; Fontana, Itiana V.; Althaus, Juciele C.; Sandri, Andréia; Rambo, Ethel V.; Stumm, Eniva M. F.; Gottems, Rúbia; Demari, Letícia; Wondracek, Letícia; Machado, Carmen R. T.; Paschoal, Fernanda; et al. (Salão do Conhecimento, 2013)
Resumo